Design of a Capacitive Level Sensor for Nitroglycerin Synthesis - A’inul Yaqin, Sa’id; Mochammad Rusli; Bambang Siswojo; Taufik (Faculty of Engineering, Universitas Brawijaya, 2025)
The synthesis of nitroglycerin requires extremely precise control of reactant volumes due to its highly sensitive and hazardous nature. This study evaluates the performance of a capacitive level sensor integrated with a Fuzzy-PID controller capable of adapting to error dynamics while utilizing an ESP32 microcontroller and a peristaltic pump. The sensor was tested for accuracy, precision, linearity, resolution, response time, hysteresis, stability, and sensitivity. The results demonstrated an accuracy of 99.4%, an R² value of 0.997, a resolution of 0.1 mL, and a response time of 4.98 seconds. The system exhibited high precision and stable performance, offering a potential solution for enhancing the reliability and safety of nitroglycerin production.